ANALISIS PENTINGNYA MENINGKATKAN STRATEGI PEMASARAN SYARIAH DI ERA DIGITAL ANALYSIS OF THE IMPORTANCE OF IMPROVING SYARIAH MARKETING STRATEGIES IN THE DIGITAL ERA - Wati, Dwi Indar; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This study discusses the importance of improving sharia marketing strategies in the digital era, where sharia companies are faced with the challenge of adapting to increasingly complex changes in consumer behavior due to advances in information and communication technology. The purpose of this study is expected to contribute to the development of more effective marketing strategies for sharia companies and provide a better understanding of sharia consumer behavior in the digital era. The method used is a descriptive qualitative method with secondary data collection to analyze important elements in sharia marketing strategies, including products, prices, places, and promotions. It is emphasized that honesty, fairness, and openness in transactions are the main principles, based on the concept of Islamic trade or commercial agreements according to sharia. Various digital marketing strategies, such as online advertising, email marketing, and social media platforms, are identified as effective tools for communicating with consumers and promoting products. In addition, the importance of conducting employee training and using online advertising in accordance with Islamic principles. In conclusion, sharia companies need to develop effective digital marketing strategies to maximize opportunities in the digital era while adhering to Islamic values, as well as complying with Islamic ethical principles in business, including transparency, legal compliance, and social responsibility.